Analysis and Optimization of Passenger Flowlines at Zhongchuan High-Speed Railway Station. (8th July 2018) - Wang, Hualan; Wang, Baoli; Xu, Jiaying; Hu, Zunjie
Abstract : In order to optimize the passenger flowlines and improve the operation capacity of Zhongchuan high-speed railway station, the simulation model of passenger flowlines is established based on the simulation software of Anylogic. The simulation of the passenger flowlines during peak and off-peak hours of the station are carried out respectively. The organization problems of passenger flowlines during peak hours are found out, and the optimization methods are put forward. The station capacity after optimization is compared with the original by employed the simulation model. The result shows, after optimization, although the walking distance of passengers who are entering the ticket hall to buy ticket is increased but the flowline separation effect is achieved, the flowlines become more clear, the cross interferences are reduced, and the station capacity is increased.